Mind the gap! Global cities and ordinary cities in the planning perspective - Silvia Ciccarelli; Roberta Gemmiti; Luca Salvati (European Regional Science Association (ERSA), 2011)
This paper presents a critical debate about the extreme selectivity through which the existing body of literature identifies the critical factors in urban development and competitiveness. It highlights the need to establish policies aimed at "ordinary cities" (Amine Graham, 1997) and "ordinary geographies" (Jonas e Ward, 2007). By analyzing the case of Rome, Italy, the paper explores the consequences of such literature for planning choices, especially for those cities that are not supported by a mature system of governance. It is well established that cities and urban regions are considered the most significant organizational and social units in the post-industrial era. The academic focus on urban regions was a result of the convergence between studies on competitiveness and disciplines like Regional Economy and Economic Geography, which tended to focus on the relationship between post-industrial capitalism and the process of regionalization. Since the first studies on industrial de-verticalization and on emerging patterns of production localization, the literature has increasingly related the economic success of firms to specific characters of territories, including face-to-face contacts, knowledge spill over and relationships based on trust. All cities, then, are framed to look like the leaders of the global urban hierarchy: Global City Regions and Mega City Regions, large territories combining hard and soft infrastructures, socializing spaces, multi-culturality, talent, tolerance; cities offering a network structure made up of Marshall nodes of production. The rigidity of current conceptions of urban competitiveness, supported also by international organizations (OCDE, 2006; Territorial Agenda, 2007), often leads to negative consequences for urban planning policies in cities that are not yet supported by a developed system of governance. This is the case for Rome, where planning policy has followed guidelines proposed by existing literature. The article argues that the oversimplification of urban development and competitiveness can result in planning policies divorced from the real issues, thus causing a unique set of social and environmental consequences.
Keywords: 330